Real-time adaptive estimation of decoherence timescales for a single qubit - Arshad, MJ; Bekker, C; Haylock, B; Skrzypczak, K; White, D; Griffiths, B; Gore, J; Morley, GW; Salter, P; Smith, J; Zohar, I; Finkler, A; et al. (American Physical Society, 2024)
Characterizing the time over which quantum coherence survives is critical for any implementation of quantum bits, memories, and sensors. The usual method for determining a quantum system's decoherence rate involves a suite of experiments probing the entire expected range of this parameter, and extracting the resulting estimation in postprocessing. Here we present an adaptive multiparameter Bayesian approach, based on a simple analytical update rule, to estimate the key decoherence timescales (T1, T2∗ - , and T2) and the corresponding decay exponent of a quantum system in real time, using information gained in preceding experiments. This approach reduces the time required to reach a given uncertainty by a factor up to an order of magnitude, depending on the specific experiment, compared to the standard protocol of curve fitting. A further speedup of a factor approximately 2 can be realized by performing our optimization with respect to sensitivity as opposed to variance.